Implications of cancer prior to and after heart transplantation. Issue 6 (1st July 2021) - Mudigonda, Parvathi; Berardi, Cecilia; Chetram, Vishaka; Barac, Ana; Cheng, Richard
Abstract : Cancer and cardiovascular disease share many risk factors. Due to improved survival of patients with cancer, the cohort of cancer survivors with heart failure referred for heart transplantation (HT) is growing. Specific considerations include time interval between cancer treatment and HT, risk for recurrence and risk for de novo malignancy (dnM). dnM is an important cause of post-HT morbidity and mortality, with nearly a third diagnosed with malignancy by 10 years post-HT. Compared with the age-matched general population, HT recipients have an approximately 2.5-fold to 4-fold increased risk of developing cancer. HT recipients with prior malignancy show variable cancer recurrence rates, depending on years in remission before HT: 5% recurrence if >5 years in remission, 26% recurrence if 1–5 years in remission and 63% recurrence if <1 year in remission. A myriad of mechanisms influence oncogenesis following HT, including reduced host immunosurveillance from chronic immunosuppression, influence of oncogenic viruses, and the cumulative intensity and duration of immunosuppression. Conversely, protective factors include acyclovir prophylaxis, use of proliferation signal inhibitors (PSI) and female gender. Management involves reducing immunosuppression, incorporating a PSI for immunosuppression and heightened surveillance for allograft rejection. Cancer treatment, including immunotherapy, may be cardiotoxic and lead to graft failure or rejection. Additionally, there exists a competing risk to reduce immunosuppression to improve cancer outcomes, which may increase risk for rejection. A multidisciplinary cardio-oncology team approach is recommended to optimise care and should include an oncologist, transplant cardiologist, transplant pharmacist, palliative care, transplant coordinator and cardio-oncologist.